2024
DOI: 10.1073/pnas.2314606121
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous virophages are active and mitigate giant virus infection in the marine protist Cafeteria burkhardae

Anna Koslová,
Thomas Hackl,
Felix Bade
et al.

Abstract: Endogenous viral elements (EVEs) are common genetic passengers in various protists. Some EVEs represent viral fossils, whereas others are still active. The marine heterotrophic flagellate Cafeteria burkhardae contains several EVE types related to the virophage mavirus, a small DNA virus that parasitizes the lytic giant virus CroV. We hypothesized that endogenous virophages may act as an antiviral defense system in protists, but no protective effect of virophages in wild host populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…For the host strain E4-10, which we used here, EMALE04 was reactivated by CroV infections but low copies were produced, and host died within several days after infection. However, they also showed that EMALE04 inhibition of the virus can amplify in subsequent rounds of infection reaching similar inhibition levels of the virus population as Mavirus (Koslová et al 2024). Whether and how EMALE04 reactivated and competed with Mavirus in our experiment is not known.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For the host strain E4-10, which we used here, EMALE04 was reactivated by CroV infections but low copies were produced, and host died within several days after infection. However, they also showed that EMALE04 inhibition of the virus can amplify in subsequent rounds of infection reaching similar inhibition levels of the virus population as Mavirus (Koslová et al 2024). Whether and how EMALE04 reactivated and competed with Mavirus in our experiment is not known.…”
Section: Discussionmentioning
confidence: 98%
“…It is thus possible that other EMALEs have been reactivated affecting the ecological and/or evolutionary dynamics. Koslová et al (2024) characterized the reactivation of EMALES in a collection of globally distributed Cafeteria populations and they found that reactivation was stochastic, inefficient and EMALE-virus specific (e.g., only one out of eight EMALEs reactivate upon CroV infection). For the host strain E4-10, which we used here, EMALE04 was reactivated by CroV infections but low copies were produced, and host died within several days after infection.…”
Section: Discussionmentioning
confidence: 99%